A robot for verifying the precision of total reaction time measurement - Tânia Brusque Crocetta; Tiago Kroich; Argeu Carlos Thiesen; Lucas Borges; Noé Gomes Borges Júnior; Luiz Carlos de Abreu; Alexandro Andrade (Universidade Estadual Paulista (UNESP), 2015)
The level of variability in psychomotor behavior and the use of several distinct sets of equipments in Reaction Time (RT) assessments might jeopardize the validity and reliability of such measures. This study presents the development and verification of Emboici Robot-a robot capable of performing accurate RT assessments consisting of response to a visual stimulus by pressing a button-whose purpose is to measure the accuracy of RT assessments. We evaluated the accuracy and precision on four different days, each providing 300 measurements. These assessments generated a RT of 46.95ms (+6.04). No significant effects were found in the RTs obtained and, as a result, there is evidence that the Emboici Robotis stable, reliable, and precise. The robot can be a viable solution for verifying precision and accuracy of any given software with simple RT assessments with visual stimulus requiring as response the pressing of a button or key.